Analisis Regresi Data Panel Pengaruh PDRB, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka terhadap Jumlah Kemiskinan di Kabupaten/Kota di Jawa Barat pada Tahun 2013-2020 - Sarah Farida Fitria (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Economic development in Indonesia is currently facing the problem of poverty. One indicator of the success of the implementation of development that can be used as a benchmark at a macro level is economic growth. Regional economic growth can be reflected in changes in Gross Regional Domestic Product in a region. In this development, humans are used as the main source of wealth in a country. This makes the Human Development Index measure the achievement of human development based on a number of basic components of quality of life. Development is carried out to realize community prosperity through economic development in overcoming various development and social problems such as unemployment. Increasing economic growth means that the production of goods/services produced will increase. The best solution in solving the problem of poverty by analyzing the influence of GRDP, HDI, and TPT on the amount of poverty in the Regency/City of West Java Province in 2013-2020. The Panel Data Regression method is used as an analytical tool in the study, by selecting the Fixed Effect Model, it shows that the GRDP, HDI, and TPT variables have a positive and significant effect on the number of poverty in districts/cities in West Java Province. Abstrak. Pembangunan ekonomi di Indonesia saat ini sedang dihadapkan pada masalah kemiskinan. Salah satu indikator keberhasilan pelaksanaan pembangunan yang dapat dijadikan tolak ukur secara makro adalah pertumbuhan ekonomi. Pertumbuhan ekonomi daerah dapat dicerminkan dari perubahan Produk Domestik Regional Bruto dalam suatu wilayah. Dalam pembangunan tersebut manusia dijadikan sumber kekayaan utama dalam suatu negara. Hal ini menjadikan Indeks Pembangunan Manusia mengukur capaian pembangunan manusia berbasis sejumlah komponen dasar kualitas hidup. Pembangunan dilakukan untuk mewujudkan kemakmuran masyarakat melalui pengembangan perekonomian dalam mengatasi berbagai permasalahan pembangunan dan sosial kemasyarakatan seperti pengangguran. Pertumbuhan ekonomi yang semakin meningkat berarti produksi barang/jasa yang dihasilkan akan meningkat. Solusi terbaik dalam pemecahan masalah kemiskinan dengan menganalisis pengaruh PDRB, IPM, dan TPT terhadap jumlah kemiskinan di Kabupaten/Kota Provinsi Jawa Barat pada Tahun 2013-2020. Metode Regresi Data Panel digunakan sebagai alat analisis dalam penelitian, dengan memilih Fixed Effect Model menunjukkan variabel PDRB, IPM, dan TPT berpengaruh positif dan signifikan terhadap jumlah kemiskinan Kabupaten/Kota di Provinsi Jawa Barat.